Anthropomorphic Figurines from Tripolye-Cucuteni: Decor Peculiarities and Its Interpretation - Mitina, Maria N. (Actual Problems of Theory and History of Art, 2016)
The article deals with the figurines of Tripolye-Cucuteni and the problem of its decor interpretation. The analysis of the decoration of the majority of the statuettes, namely almost a complete covering of the figurines’ surfaces with decor and the rhythm of linings, suggests its close similarity with textile ornaments. The aim of the article was to find evidence that the decor of the figures mostly resembles garments. Their linear depiction marks out the statuettes of Neolith and the Bronze Age in Europe from the figurines of subsequent periods. The interpretation problem of these figurines is still unsolved. Because of the variety of forms and decorations, we cannot solve this problem through unequivocal assumptions that suchfigures are the images of gods and goddesses of the early agricultural pantheon. It would be more productive to concede that at least some figures are the images of real or mythical ancestors such as ancient Lares and Penates. In this case, the research of the statue decor and the clothes, as an attribute of a character, allows for further concretization of the characters and their place in the structure of ancient European art.
Keywords: figurines; Tripolye-Cucuteni; Neolithic-Chalcolithic art; clothes; art history